The Causal Effect of Authentic Leadership on Employee Performance in Logistics Company with Positive Psychological Capital as a Mediator - Chaiwisit, Nichakorn; Surakarn, Amaraporn; Kleebbua, Chaiyut (Dusit Thani College Journal, 2022)
The objective of this research are to study the causal relationship of Authentic Leadership on employee performance in logistics company with Positive Psychological Capital as a mediator. This study used a causal research methodology and Collecting data from online questionnaires. The sampling were 170 full-time employees of a logistics company and analyzing by use Structural Equation Modeling (SEM). The results showed that the causal effect model was in accord with the empirical data 𝑥2= 38.20, df = 31, 𝑥2/df = 1.23, P-Value = 0.18, RMSEA = 0.04, CFI = 1.00, TLI = 0.99, SRMR = 0.03 and all of the variables in the model explained 29 percent of performance variance. It was also found that Authentic Leadership had a significant total effect on employee performance (b=0.44, p<0.05). Authentic Leadership had a positive significant direct effect on employee performance (b=0.34, p< 0.05) and Authentic Leadership had a significant indirect effect on employee performance through Positive Psychological Capital (b=0.10, p<0.05). The indirect effects showed that Authentic Leadership had a positive and significant effect on the Positive Psychological Capital of the employees (b=0.33, p<0.05) and Positive Psychological Capital had a positive significant effect on employee performance (b=0.31, p<0.05). The results showed the importance of the Authentic Leadership of supervisors and the Positive Psychological Capital of the employees in terms of performance. The results of this research will help to improve Authentic Leadership and Positive psychological capital of logistics company employees and can enhance employee performance.